A systematic review of passive energy consumption optimisation strategy selection for buildings through multiple criteria decision-making techniques. (January 2023) - Balali, Amirhossein; Yunusa-Kaltungo, Akilu; Edwards, Rodger
Abstract: Buildings account for a significant proportion of global energy demand, which is testament to population growth and changes to life patterns. Experts in energy studies have continued to identify passive energy consumption optimisation strategies as viable approaches for curbing the menace of steadily rising energy demand in buildings. However, the implementation of a logical procedure for selecting suitable passive strategies for use in buildings remains a challenge. Also, existing studies have mainly focused on a very limited number of passive strategies, selection criteria and selection methods. Therefore, this study aims to generate a very comprehensive list of the most prevalent passive energy consumption optimisation strategies, their selection criteria, and the multiple criteria decision analysis/making (MCDA/MCDM) techniques that aided the selection process, via a combination of preferred reporting items for systematic reviews and meta-analyses (PRISMA) and procedure for performing systematic reviews (PPSR) approaches. To ensure comprehensiveness, the study extracted information from a wide range of large and multidisciplinary databases (such as Web of Science and Scopus) as well as smaller but engineering and science disciplines specific databases (such as Compendex, GEOBASE, GeoRef, and Inspec). It was concluded that the existing literature focused on a very small number of passive strategies especially optimizing the insulation layer, using naturally ventilated envelope, and using sun shading devices. Cost and energy saving potentials were considered as the selection criteria in most of the previous studies, and analytical hierarchy process (AHP) was the most popular selection technique, which may not be suitable for under all scenarios. Graphical abstract: Image 1 Highlights: PRISMA-based systematic literature review of passive strategies in buildings. Identifying passive energy consumption optimisation strategies in buildings. Identifying relevant criteria for best passive strategy selection. Identifying multiple criteria decision making techniques for the selection process.